Multiplexing real time video services - Simón, María (1999)
Statistical Bit Rate (SBR) transfer capability is considered a good option for supporting Variable Bit Rate (VBR) services. However, its study is somewhat in lag compared with Deterministic Bit Rate (DBR) or Available Bit Rate (ABR) capabilities. The definition of a general Call Acceptance Control (CAC) function is difficult to state for SBR. We present some results regarding the multiplexing of real time data streams, mainly from interactive video services, wich ara naturally VBR an therefore candidates to use the SBR capability. It is shown that image quality is improved by using SBR instead of DBR. The coder design does not become more complicated. In fact, it remains the same. We propose a statistical model for the traffic generated by such video sources. The delays introduced by a switch are studied following two approaches. Exact bounds are found for a worst ase situation, indicating a very low statistical gain. However, simulations show that these bounds are too pessimistic since the worst case very rarely occurs. A very high mean load can be reached with acceptable delays. Indeed, the statistical gain is found to be significant The CAC for this kind of service may be simple because, even assuming pessimistic figures, the burstiness for a real-time video data stream appears to be low.